Assessment of Science Laboratory Resources in Public High Schools - Achacoso, Daileen; Bapilar, Mauricia (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the science laboratory resources in public secondary schools in the CAMAG districts of Bohol Division during School Year 2025–2026. Anchored on Human Capital Theory and Diffusion of Innovation Theory, the study examined the availability, functionality, and extent of utilization of DepEd-provided laboratory resources, as well as the relationship between laboratory utilization and teachers’ educational qualifications, years of science teaching experience, and laboratory-related training attendance. An explanatory sequential mixed-methods design was employed, involving 65 science teacher-participants selected through total enumeration. Data were gathered using a researcher-made survey questionnaire and semi-structured interview guide. Quantitative data were analyzed using frequency, percentage, mean, standard deviation, and Spearman correlation, while qualitative data were analyzed through thematic analysis. Findings showed that most laboratory resources were generally available and functional, but physics and STEM chemistry resources were limited, and several resources across integrated science, chemistry, physics, SHS Core, STEM chemistry, and STEM physics were underutilized. Educational attainment had a significant but small positive relationship with laboratory utilization, while years of science teaching experience and laboratory-related training showed strong positive relationships. Low utilization was attributed to inadequate and misaligned laboratory infrastructure, insufficient teacher skills and training, limited time for laboratory activities, and curriculum–laboratory misalignment. The study recommends upgrading laboratory resources, strengthening specialized laboratory training, aligning curriculum requirements with laboratory activities, and providing sufficient time for laboratory work. The study supports SDG 4—Quality Education by promoting improved science learning environments and teacher capacity. Its sustainability impact lies in strengthening educational, institutional, governance, and innovation sustainability through better laboratory management, resource utilization, and science instruction.